2021
DOI: 10.1177/2045894021996224
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients hospitalized for acute pulmonary embolism by obstructive sleep apnea status

Abstract: Pulmonary embolism (PE) is a major cause of cardiovascular morbidity and mortality. Obstructive sleep apnea (OSA) is increasingly recognized in the ageing population, especially with the rising obesity epidemic. The impact of OSA on inpatient mortality in PE is not well understood. We used the Nationwide Inpatient Sample databases from 2005 to 2016 to identify 755,532 acute PE patients (age18 years). Among these 61,050 (8.1%) were OSA+. Temporal trends in length of stay (LOS), inpatient mortality and its as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…As might be expected, NIV was more common in men and women with OSA than in those without OSA, possibly because the former may have had more severe PE or hypoxemia 26 . Nevertheless, NIV was not a predictor of IHM in OSA patients admitted with PE.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As might be expected, NIV was more common in men and women with OSA than in those without OSA, possibly because the former may have had more severe PE or hypoxemia 26 . Nevertheless, NIV was not a predictor of IHM in OSA patients admitted with PE.…”
Section: Discussionsupporting
confidence: 64%
“…The potential resulting protective effect could be associated with lower mortality. This explanation could justify the findings of Joshi et al 26 , who reported prevalent OSA to be associated with lower IHM in PE patients. The same authors also suggested that OSA could lead to increased hemoglobin levels resulting from hypoxemia, which may confer a protective effect in acute PE by preventing hypoxia from worsening 14 , 26 .…”
Section: Discussionsupporting
confidence: 54%
“…These findings were confirmed independently in a more recent study [ 35 ]. Similarly, other recent publications involving patients hospitalized for myocardial infarction [ 25 , 27 ], pulmonary embolism [ 29 ] and critically ill patients [ 36 ], showed a decrease of in-hospital mortality associated with diagnosed SA. The mechanisms underlying these findings are incompletely understood.…”
Section: Discussionsupporting
confidence: 57%
“…The outcome of hospitalized patients with SA has only been scarcely investigated and is still controversial [ 24 , 25 ]. Patients with SA typically have a greater burden of comordities, use more hospital resources [ 26 ] but, for certain conditions (including myocardial infarction, pneumonia, pulmonary embolism), have a lower inpatient mortality [ 25 , 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…After evaluation of full-texts 11 were excluded as they did not satisfy the inclusion criteria. Finally, 12 studies were included in the present review (8)(9)(10)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%